STUDI PEMIKIRAN SYAYKH PANJI GUMILANG TENTANG BUDAYA TOLERANSI DAN PERDAMAIAN DI MA'HAD AL-ZAYTUN: Analisis Pemikiran Syaykh Panji Gumilang Mengenai Toleransi Dan Perdamaian: Pendekatan Studi Pemikiran Islam - Vina Alfiyah; Riska Safriyanti; Santoso; Agus Rojak Samsuddin (Institut Agama Islam Sumatera Barat Pariaman, 2025)
This study examines Syaykh Panji Gumilang’s thought on the concepts of tolerance and peace and their relevance to educational practices at Ma’had Al-Zaytun. The research employs a library-based qualitative approach using figure study methods and content analysis of written works, speeches, and institutional documents. The study is limited to a conceptual examination and does not evaluate the controversial aspects or socio-political practices related to the figure. The findings indicate that Syaykh Panji Gumilang’s ideas emphasize openness, respect for diversity, and the cultivation of a culture of peace within Islamic educational contexts. These concepts align with multicultural education theory, Johan Galtung’s positive peace framework, and the principles of maqasid al-shari‘ah. This study contributes to the enrichment of contemporary Islamic education literature, particularly concerning efforts to foster tolerance and peace within educational institutions.